The imitation game [videorecording (DVD)] - Cumberbatch, Benedict, 1976-; Knightley, Keira, 1985-; Strong, Mark, 1963-; Kinnear, Rory, 1978-; Hodges, Andrew (Anchor Bay Entertainment, 2015)
During the winter of 1952, British authorities entered the home of mathematician, cryptanalyst and war hero Alan Turing to investigate a reported burglary. They instead ended up arresting Turing himself on charges of "gross indecency," an accusation that would lead to his devastating conviction for the criminal offense of homosexuality - little did officials know, they were actually incriminating the pioneer of modern-day computing. Famously leading a motley group of scholars, linguists, chess champions and intelligence officers, he was credited with cracking the so-called unbreakable codes of Germany's World War II Enigma machine. An intense and haunting portrayal of a brilliant, complicated man, "The Imitation Game" a genius who under nail-biting pressure helped to shorten the war and, in turn, save thousands of lives.